Violence and territorial order in Caracas, Venezuela. (October 2020) - Antillano, Andrés; Arias, Enrique Desmond; Zubillaga, Verónica
Abstract: In 2015, Caracas, Venezuela, had a homicide rate of 75 per 100, 000 inhabitants, which made it one of the most violent cities in the world that year. Despite these high rates of violence, the international community knows relatively little about the dynamics underlying conflict in the city. Through a systematic comparison of three poor and working-class neighborhoods in the Caracas metropolitan area, this article analyzes the factors that have driven these remarkably high rates of violence, as well as those factors that have configured the heterogeneous violent conditions that operate across the city. Building on extensive interviews in these neighborhoods, we argue that the levels of violence in particular locales derive from the ways in which the Bolivarian political regime failed in its efforts to incorporate the poor and working-class inhabitants of different parts of the metropolitan area into the political, social, and economic systems that dominate the country today. We also argue that variation in violence results from the way in which certain neighborhoods are geographically inserted into local illicit economies and the political and social dynamics of an increasingly violent and unstable political system.